2020
DOI: 10.3892/mmr.2020.11217
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoplasmic reticulum oxidase 1α in H9C2 cardiomyocytes following hypoxia/reoxygenation injury

Abstract: endoplasmic reticulum (er) oxidase 1α (ero1α) is a glycosylated flavoenzyme that is located on the luminal side of the ER membrane, which serves an important role in catalyzing the formation of protein disulfide bonds and ER redox homeostasis. However, the role of ERO1α in myocardial hypoxia/reoxygenation (H/R) injury remains largely unknown. In the present study, ERO1α expression levels in H9C2 cardiomyocytes increased following H/R, reaching their highest levels following 3 h of hypoxia and 6 h of reoxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Therefore, Dex exerted its protective effects via the inhibition of the intrinsic pathway. Because ER stress is known to be essential for H/R‐induced apoptosis, 10 the effects of Dex on ER stress were examined. The H/R treatment induced the upregulation of GRP78 and CHOP (Figure 3I).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Dex exerted its protective effects via the inhibition of the intrinsic pathway. Because ER stress is known to be essential for H/R‐induced apoptosis, 10 the effects of Dex on ER stress were examined. The H/R treatment induced the upregulation of GRP78 and CHOP (Figure 3I).…”
Section: Resultsmentioning
confidence: 99%
“…Endoplasmic reticulum oxidoreductase 1α (Ero1α), an ER-resident sulfhydryl oxidase, is responsible for catalyzing disulfide bond formation in nascent polypeptide substrates [19]. It has been found that increased Ero1α is involved in the development of ER stress-induced vascular endothelial dysfunction [20] and cardiomyopathy [21,22]. Upregulation of Ero1α exacerbates ER stress, and leads to cell death [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…1B ) in a concentration-dependent manner, suggesting a modulatory effect of Dancr on cardiomyocyte ERS. Based on the finding that 2.5 µM Tm resulted in a >50% reduction in Dancr expression but maintained cell viability at ≥50%, 2.5 µM Tm was selected for subsequent experiments ( 39 ).…”
Section: Resultsmentioning
confidence: 99%